Numerical calculation of the recirculation factor in flameless furnaces (2013)
This paper performs calculations of the recirculation factor in simulations of a flameless combustion furnace with different percentages of oxygen in air (from 21% to 100% O2). Results are compared with Magnussen’s recirculation theory and show that when there are chemical reactions, the recirculation results are overpredicted. An alternative correlation to Magnussen’s theory is proposed, useful in calculating the recirculation factor in flameless furnaces. Also, calculation of the recirculation factor obtained through numerical simulation for different configurations of confined jets taken from literature which do not involve chemical reactions, when compared with the recirculation confined jet theories of Craya-Curtet, Thring-Newby and Magnussen show that as recirculation increases, all the theories overpredict the recirculation factor.